2012
DOI: 10.1037/a0025923
|View full text |Cite
|
Sign up to set email alerts
|

Drive for muscularity and help-seeking: The mediational role of gender role conflict, self-stigma, and attitudes.

Abstract: Men with greater gender role conflict (GRC) tend to exhibit a variety of body image concerns, including a drive for muscularity (DM). In accordance with the theory of planned behavior (TPB), men with higher levels of GRC also report negative attitudes and a lack of intentions to seek help for problems. Additionally, prior research regarding other individual and contextual help-seeking related variables has shown that men with higher GRC report increased stigma of both seeking help and having mental health prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 51 publications
1
26
3
Order By: Relevance
“…Usually studies support the idea that women possess more positive attitudes towards mental help and counselling than men due to the traditional male gender role (Vogel, Wade, & Hackler, 2007). Men are expected to be independent, strong and controlling, therefore seeking of mental help threatens their self-esteem (Shepherd, & Rickard, 2012). Contradictory results might be explained by the small number of male participants in our sample.…”
contrasting
confidence: 47%
See 1 more Smart Citation
“…Usually studies support the idea that women possess more positive attitudes towards mental help and counselling than men due to the traditional male gender role (Vogel, Wade, & Hackler, 2007). Men are expected to be independent, strong and controlling, therefore seeking of mental help threatens their self-esteem (Shepherd, & Rickard, 2012). Contradictory results might be explained by the small number of male participants in our sample.…”
contrasting
confidence: 47%
“…(2) Is this relation sensitive to socio-demographic and organizational factors? Former studies propose that socio-demographic factors have non-significant impact on burnout (Bria et al, 2012), whereas help seeking stigma might be gender, culture or ethnicity biased (Cheng, Kwan, & Sevig, 2013;Shepherd, & Rickard, 2012). Also some researchers found out that psychiatrists and non-medical mental health professionals differ in burnout levels (Volpe et al, 2014).…”
mentioning
confidence: 99%
“…For example, men may avoid counselling and express dominance over others as compensatory behaviour for their perceptions of their own bodies [55]. Shepherd and Rickard [57] found that men with an increased drive for muscularity are less likely to seek help for their body dissatisfaction, which increases the risk of poor mental health. Consequently, these feelings and behaviours could worsen if associated with anxiety and depression, as they could intensify men's vulnerability caused by body dissatisfaction, and ultimately lead to a breakdown in relationships and negativity in social settings.…”
Section: Discussionmentioning
confidence: 99%
“…Gender role conflict has been consistently identified as having an association with more negative attitudes toward counseling (e.g., Pederson & Vogel, 2007;Shepherd & Rickard, 2012;Wester, Arndt, Sedivy, & Arndt, 2010). This issue has been studied almost exclusively in men as a method of further exploring how masculine norms might influence attitudes.…”
Section: Attitudes and Intentions To Seek Help In The General Populationmentioning
confidence: 99%